Structural change and the National Initiative for Human Development in Morocco: Subnational insights - Al-mouksit Akim; Wissal Sahel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper aims to revisit the pace and patterns of structural change in Morocco with a renewed perspective focusing on subnational trends to document the macro patterns. In that perspective, we first build a within-country sectoral longitudinal dataset covering employment and value added (VA) that expands the international databases mostly used in the literature. Based on this novel dataset, our results shed light on the different contributions of subnational units (regions) to labour productivity growth and, subsequently, structural change. Taking advantage of this novel dataset, we use an instrumental variable (IV) strategy to estimate the impact of the National Initiative for Human Development (NIHD) programme on labour productivity growth and both of its components: the between (structural change) and the within components. We find that the NIHD programme positively affects productivity growth overall, mainly through structural change. The results are driven by urban areas and the participation of local actors such as associations or cooperatives in the management of NIHD projects.
Keywords: O10; O14; O18; O47; 330; structural change; human development; subnational; Morocco